Virtual immediate feedback with POCUS in Belize - Mulye, Anita; Bhasin, Ajay; Borger, Bonita; Fant, Colleen (Frontiers in Digital Health, 2023)
Point of care ultrasound (POCUS) is a portable and accessible tool that has immense potential in low- and middle-income countries (LMIC) for diagnostic accuracy and medical education. We implemented a hybrid in-person and virtual training curriculum to teach providers in Belize the basic techniques of lung ultrasound in the diagnosis of pneumonia. Between August 2021 and June 2022, a total of eleven lung scans were performed at Hillside Clinic for patients presenting with respiratory complaints. Deidentified images were shared via the ButterflyIQ web platform to POCUS experts in the United States. We found that training was solidified through virtual, immediate feedback using the common interfaces Butterfly iQ + and WhatsApp to share images and guide diagnostic reasoning. The aim of this review study is to share our experience and challenges in the implementation of a POCUS training curriculum in an LMIC, provide an example of training methodology that can be effective, and discuss how this can be implemented and modified for clinicians in similar settings.